Principles of foundation engineering - Das, Braja M. 1941 (Cengage Learning, 2019)
"A must-have resource for all foundation engineering courses, Principles of Foundation Engineering, 9th Edition provides a careful balance between current research and practical field applications as it introduces civil engineering students to the core concepts and applications of foundation analysis design. Throughout this best-selling book, Dr. Das and Dr. Sivakugan emphasize how to develop the critical judgment civil engineers need to properly apply theories and analysis to the evaluation of soils and foundation design. This new edition includes three new chapters that highlight developing topics. This edition also provides a wealth of worked-out examples and multiple new figures that emphasize the skills most critical for students to master as successful civil engineers." -- Provided by publisher